Contested conversions to Islam : narratives of religious change in the early modern Ottoman Empire - Krstić, Tijana (Stanford University Press, 2011)
This work explores how Ottoman Muslims and Christians understood the phenomenon of conversion to Islam from the 15th to the 17th centuries, when the Ottoman Empire was at the height of its power and conversions to Islam peaked.